Doctorate in Educational Leadership for Equity and Justice (DELEJ) Flyer
CSUCI's Ed. D. in Educational Leadership for Equity and Justice is on track to launch in Summer 2024 (pending WSCUC approval). Candidates who hold an MA or MS degree and aspire to leadership positions in P-12 with Administrative Services Credential, Higher Education, Early Childhood, and Special Education are encouraged to apply.